Pembinaan dan Evaluasi Kursus Perwira Bagi Personel TNI Angkatan Laut pada Prodi Potensi Maritim - Saptono, Dwi; Hermawan, Romy; Bandono, Adi (LPPM Universitas Trunojoyo Madura, 2023)
Suspapotmar is a series of military education activities in the Indonesian Navy which aims to organize and process educational operational equipment (katopsdik), which consists of ten components: curriculum, instruction packages, teaching staff, educational staff, students, teaching methods, alins/alongins, facilities education, educational evaluation, and budget, to achieve educational goals. All stages of course delivery must be evaluated to ensure that education is carried out correctly and effectively. Where each action runs separately or simultaneously. The implementation of Suspapotmar in Kodiklatal is inseparable from the Indonesian Navy's Education Quality Standards, which are an important component in improving educational management and the quality of educational outcomes, which helps the Indonesian Navy achieve its vision of becoming world class. It is very important for the Kodiklatal educational institution to organize the Suspapotmar course program, because apart from this course it is also needed for Serdik and is in accordance with the needs of the organization and Indonesian Navy soldiers. Not infrequently, after students complete the course and return to their workplace, they can experience problems. Therefore, evaluation will determine whether the learning program is running well. Data analysis techniques using qualitative research analysis are carried out starting from the stage of entering the object, while at the object and at the end of the object. So the results show that the determination of Suspapotmar students is in accordance with the required classification and has gone quite well. From observations in the field, all teaching staff have taken the required education. From the results of interviews with students and teaching staff, researchers received input stating that the facilities had been met. And based on expert information, the education budget is well supported and has been implemented according to established mechanisms, including fulfilling the rights of students.